KERAGAAN AGROINDUSTRI KOPI BUBUK (Studi Kasus pada Agroindustri Kopi Selangit di Kabupaten Musi Rawas) - Wahyuni, Nenny (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2021)
Coffee plant at Selangit Regency is unique, coffee was plant under rubber plant between durian plant. The existence of coffee plant has bring up industry of coffee powder since 2007. In 2013 coffee powder industry get attention from Musi Rawas Regency government under founding of KPH Musi Rawas and release prime product of coffee with brand â€œKopi Selangitâ€. The purpose of this research was to identifird performance of coffe powder industry and analize the benefit of Kopi Selangit industry at Musi Rawas Regency.Â The research method used was case study, with respondence choosen purposively.The result of this study shows that production of coffee powder has variative measurement and packaging. The production of Kopi Selangit as much as 140 kg per month or 1.680 kg per year.Â Benefit from this production as much as Rp. 4.696.487 per month with 5 times production, and this industry categorize as capital intensive industry.